2014
DOI: 10.1117/12.2047854
|View full text |Cite
|
Sign up to set email alerts
|

Shading and shadowing on Canaletto's Piazza San Marco

Abstract: Whereas the 17th century painter Canaletto was a master in linear perspective of the architectural elements, he seems to have had considerable difficulty with linear perspective of shadows. A common trick to avoid shadow perspective problems is to set the (solar) illumination direction parallel to the projection screen. We investigated in one painting where Canaletto clearly used this trick, whether he followed this light direction choice consistently through in how he shades the persons. We approached this qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Naturally, the use of the probe in paintings has certain limitations, for instance we do not know the exact geometry of the scene and the materials of objects. Furthermore, we cannot conclude without doubt, whether the ambiguity of the settings occurred due to observers confusion or due to an artist representation of a light field, as it was demonstrated by Wijntjes in Canaletto paintings 4 . Canaletto drew the shadows parallel to the projection screen and used different shading than the parallel light direction would predict.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Naturally, the use of the probe in paintings has certain limitations, for instance we do not know the exact geometry of the scene and the materials of objects. Furthermore, we cannot conclude without doubt, whether the ambiguity of the settings occurred due to observers confusion or due to an artist representation of a light field, as it was demonstrated by Wijntjes in Canaletto paintings 4 . Canaletto drew the shadows parallel to the projection screen and used different shading than the parallel light direction would predict.…”
Section: Discussionmentioning
confidence: 93%
“…This drove our attention to lighting in paintings: faithful at first glance, is it accurate and consistent in details? Wijntjes and de Ridder 4 has already approached the topic with his study of objects' shadows and shading in Canaletto paintings, in which he points out that the artist probably rendered the shading inconsistently with the shadowing. In our research we shift the focus from object lighting to a comparison between local and global light structure in paintings.…”
Section: Introductionmentioning
confidence: 99%
“…Shadows are another interesting aspect of the paintings. A recent study showed that Canaletto had considerable difficulty with shadows in depth (Wijntjes and de Ridder, 2014). A common trick to avoid shadow perspective problems is to paint the shadows parallel to the canvas.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting trick to avoid making perspective mistakes is to organize sunrays parallel to the projection plane. In that case, the cast shadows will also be parallel and do not need to converge, a convention that is often used by Canaletto (Wijntjes & de Ridder, 2014;Wijntjes, 2020).…”
Section: Color and Lightmentioning
confidence: 99%